Expresión ¬(¬a∨¬b∧(a∨c)∨b∧((¬(a∨c))))
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
¬(a∨c)=¬a∧¬cb∧¬(a∨c)=b∧¬a∧¬c(b∧¬(a∨c))∨(¬b∧(a∨c))∨¬a=¬a∨¬b¬((b∧¬(a∨c))∨(¬b∧(a∨c))∨¬a)=a∧b
Tabla de verdad
+---+---+---+--------+
| a | b | c | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 0 |
+---+---+---+--------+
| 0 | 1 | 1 | 0 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 1 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+